Representações sociais de professores sobre a inserção/intervenção pedagógica da educação física na educação infantil de Serra - Jesus, Joíse Fernandes de (2014)
Identifies and analyzes the social representations of teachers on the inclusion/intervention of Physical Education in the context of early childhood education from Serra, ES. This is a qualitative study, with descriptive and interpretive approach, which used semi-structured and elite interviews as sources in compiling the data. Interviews were held with 12 permanent teachers, sample corresponding to 60% of the total population of the Physical Education teachers working at this level of education, and the manager of Childhood Education of the municipality. The data were interpreted by Content Analysis, considering the social-interactional context in which they were produced. Social representations, generated in communicative activities of different discourse communities, are psychological structures that individuals use to think or act in everyday situations (MOSCOVICI, 2003). They correspond to a practical knowledge that subjects mobilize to deal with their reality. The data analyzed evidence that physical education was inserted in Early Childhood Education of the municipality to serve a lawsuit related to the planning necessity of the "regents teachers." Significant portion of teachers gone work for Early Childhood Education against their will, as the only alternative to complement their workload, generating resistance and misunderstandings about the specificities of children and institutions set for their education. Pedagogical perspectives adopted by teachers were not designed for this level of education or are anchored in the idea of children as a universal being, with fixed principles of development, unlike the notion of historical subject, as recommended by the Child Education Curriculum Guidelines (2013). The inclusion of physical education in the research context has generated tensions, as the struggle by physical and occupational spaces and misunderstanding of the role of the teacher in this curricular component in CMEIs. However, experiences in Early Childhood Education are contributing to the redefinition of the initial representations, favoring the construction of positive readings of this context of teaching practice